IMPROVING THE POSITION OF UZBEKISTAN IN INTERNATIONAL RATINGS AND INDEXES IN THE FORMATION OF INTERNATIONAL FINANCIAL CENTERS (American Journal of Interdisciplinary Research and Development, 2023)
In this article defining factors of methodology an evaluation of an investment climate of the country for wide attracting foreign investments into national economy, the importance of acquiring the highest sovereign credit rating of the country, actions aimed at improving the international rating and index indicators of our country, and also the scientifically-proved offers with a view of the further improvement of a favorable investment climate of Uzbekistan are given.